Communities Helping the Hearing of Infants by Reaching Parents (CHHIRP) through patient navigation: a hybrid implementation effectiveness stepped wedge trial protocol. Issue 4 (19th April 2022) - Bush, Matthew; Hatfield, Miranda; Schuh, Marissa; Balasuriya, Beverly; Mahairas, Anthony; Jacobs, Julie; Studts, Christina; Westgate, Philip; Schoenberg, Nancy; Shinn, Jennifer; Creel, Liza
Abstract : Introduction: As the most common neonatal sensory disorder in the USA, infant hearing loss has an incidence of 1.7 per 1000 births. The consequences of delayed diagnosis and failure to obtain timely intervention include significant communication impairment and negative socioeconomic effects. Early Hearing Detection and Intervention (EHDI) national standards dictate that all infants should be screened and diagnosed by 3 months of age and there is a need for interventions that promote adherence to timely diagnosis. Patient navigation (PN) has been shown to be efficacious to decrease non-adherence with infant hearing diagnostic care; however, PN has yet to be tested in diverse communities or implemented into real-world settings. Methods and analysis: The proposed research is a community-engaged, type 1 hybrid effectiveness-implementation trial of a PN intervention aimed at decreasing infant hearing diagnosis non-adherence after failed newborn hearing screening, delivered in state-funded EHDI clinics. Guided by our community advisory board and partners, we aim to (1) test the effectiveness of PN to decrease non-adherence to receipt of infant hearing diagnosis within 3 months after birth using a stepped-wedge trial design, (2) investigate implementation outcomes and factors influencing implementation and (3) determine the cost-effectiveness of PN from the perspective of third-party payers. The study will be conducted from April 2019 until March 2024. Ethics and dissemination: This protocol was approved by the University of Kentucky Institutional Review Board. Although all research involving human subjects contains some risk, there are no known serious risks anticipated from participating in this study. We will seek to disseminate our results in a systematic fashion to patients, key stakeholder, policymakers and the scientific community. Our results will impact the field by partnering with communities to inform the scale-up of this innovative patient supportive intervention to create efficient and effective EHDI programmes and maximise public health impact. Trial registration number: Clinicaltrials.gov (Pre-results phase): NCT03875339 .